Efektivitas Dokter Kecil dalam Promosi Kesehatan Gigi di Sekolah Dasar Ar Rosyid Sukoharjo - Erni Susanty Tahir; Puput Mulyono (Pusat Riset dan Inovasi Nasional, 2025)
Introduction: Dental and oral health problems in school-age children are still a major public health concern. The Little Doctor Program is a school-based health promotion approach that involves the active role of students as agents of change. This study aims to analyze the effectiveness of Small Doctors in promoting dental health in elementary schools. Methods: This study used a quasi-experimental design with a one group pretest–posttest approach. The subjects of the study were elementary school students who participated in dental health promotion activities by Small Doctors. Interventions include counseling, demonstrations of proper brushing of teeth, and the use of educational media. Data were collected using a questionnaire of dental health knowledge, attitudes, and behaviors before and after the intervention. Data analysis was carried out using the paired t-test or Wilcoxon test with a significance level of p < 0.05. Results: There was a significant improvement in students' dental health knowledge, attitudes, and behaviors after the intervention (p < 0.05). Conclusion: The Small Doctor Program is effective as a strategy for promoting dental health in elementary schools and has the potential to support promotional and preventive efforts for children's dental health.